Database Paket Kontraktual Berbasis Web - Sumiyati, Sumiyati; Nawangsasi, Yuli; Gustirani, Indri (Universitas Pendidikan Indonesia, 2018)
AbstractThe monitoring system carried out at Unit X still uses Microsoft Excel, making it less effective and frequent errors. Monitoring records have not been able to provide a warning when contractual deadlines and supplier data have not been properly recorded. So a database application is needed that can help the finance department in monitoring the contractual package. This study uses the Research and Development method. The system development method used is the Waterfall method which through several stages including Analysis, Design, Encoding, Testing, implementation and maintenance. Development of this application using the PHP and MySQL program. The results of this study indicate that the monitoring procedures that have been done manually are not optimal. The design of the contractual package database application is expected to be able to overcome the obstacles encountered before and minimize human error. The application of this application is able to facilitate the financial section in monitoring contractual packages and producing new products that are declared effective and feasible to use. Keyword : Contractual Database, Web. AbstrakSistem monitoring yang dilakukan pada Satker X masih menggunakan Microsoft Excel sehingga kurang efektif dan sering terjadi kesalahan. Pencatatan monitoring belum bisa memberikan warning ketika paket kontraktual deadline dan data – data supplier belum terekam dengan baik. Sehingga dibutuhkan aplikasi database yang dapat membantu bagian keuangan dalam memonitoring paket kotraktual. Penelitian ini menggunakan metode Research and Development. Metode pengembangan sistem yang digunakan adalah metode Waterfall yang melalui beberapa tahap diantaranya Analisis, Desain, Pengodean, Pengujian, implementasi dan pemeliharaan. Pembangunan aplikasi ini menggunakan Program PHP dan MySQL. Hasil penelitian ini menunjukkan bahwa prosedur monitoring yang telah dilakukan secara manual kurang maksimal. Perancangan aplikasi database paket kontraktual ini diharapkan mampu mengatasi kendala yang ditemui sebelumnya dan meminimalisir human error. Penerapan aplikasi ini mampu memudahkan bagian keuangan dalam monitoring paket kontraktual dan menghasilkan produk baru yang dinyatakan efektif dan layak digunakan. Kata Kunci: Database Paket Kontraktual, Web.